Modulation of DNA synthesis in porcine adipose tissue by growth hormone, insulin and leptin - H, Mohan N; Sarmah, B C; Tamuli, M K; Kalita, D; Goswami, J N; Bhattacharyya, B N; Baruah, Anubha; Das, Anubrata (The Indian Journal of Animal Sciences, 2012)
Adipose tissue plays critical role in energy homeostasis by responding to nutritional, neural, and hormonal signals and secreting adipokines that control feeding, thermogenesis, immunity, and neuroendocrine function. DNA synthesis takes place in the adipose tissue continuously due to multiplication and differentiation of various cell populations. The present study was undertaken to analyze effect of growth hormone, insulin and leptin on DNA synthesis in porcine adipose tissue under in vitro conditions and the differential distribution of thymidine incorporation among adipose and stromal-vascular fractions. Adipose tissue explants were incubated with various hormonal combinations in the media containing 3[H] thymidine and its incorporation into cell/DNA was measured later. Growth hormone, insulin and leptin increased thymidine uptake by 4.95, 2.45 and 1.85 times over the non hormonal control tissue explants. Among the combinations GH + leptin and insulin +leptin incubated groups had the lowest and highest thymidine uptake respectively. Out of the total thymidine incorporated in the adipose tissue, 90.49% of the thymidine was taken up by the stromo- vascular cells in comparison to adipocytes (9.51%) in control group. Based on the present study it can be concluded that GH, insulin and leptin increased cellular uptake of thymidine, indicating that all these hormones promoted DNA synthesis and /or multiplication in the cells and stromal vascular fraction of adipose tissue is actively involved in DNA synthesis.